Energy Drink Consumption Causes Severe Dental Erosion: An in Vitro Study - Gabriella Rodovalho Paiva; Daniella Christina da Silva Morais; Fabrícia Pacheco Ferreira; Maria Angélica Hueb de Menezes Oliveira; Vinícius Rangel Geraldo-Martins; Juliana Jendiroba Faraoni; Regina Guenka Palma Dibb; Denise Tornavoi de Castro; Janisse Martinelli de Oliveira Misiara; Cesar Penazzo Lepri (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate whether the consumption of energy drinks promotes dental erosion and assess the effectiveness of various treatments. Materials and Methods: Forty specimens of bovine root dentin were prepared (4.00 mm × 4.00 mm × 3.00 mm in thickness). For erosion, the specimens were immersed in an energy drink (pH 3.24 at 10°C) in 1-minute cycles three times a day for 5 days. After the cycles, the specimens were divided into four groups (n = 10): NT, no treatment; FV, 5% fluoride varnish; L, laser Er,Cr:YSGG; and FV+L, 5% fluoride varnish followed by application of the Er,Cr:YSGG laser. The surface roughness and the wear profile of the dentin were analyzed by confocal laser scanning microscopy. Analysis of Variance (ANOVA) and Tukey post-hoc tests were performed for the surface roughness analysis. For volume loss, the Kruskal-Wallis test was used (α=0.05). Results: There was no statistically significant difference between the groups in the control region (p>0.05) for surface roughness. In the experimental area, the NT (4.109 ± 0.184) and FV (3.850 ± 0.231) groups exhibited the highest surface roughness, with no significant difference between them. However, they showed a statistically significant difference from the L (2.058 ± 0.160) and FV+L (1.907 ± 0.179) groups (p<0.05), which also did not reveal any differences between themselves. The mean volume loss in all groups was approximately 20%, which remained after the treatments. Therefore, no statistical differences were found (p>0.05). Conclusion: The consumption of energy drinks can lead to dental erosion, resulting in volume loss and increased roughness. None of the treatments could reverse the loss of volume. The irradiated groups achieved the best results in terms of surface roughness.